Ceramics for beginners surfaces, glazes & firing - Pozo, Angelica (Lark Books, 2010)
"For the beginner, the techniques explained in this book are "like having the biggest box of crayons ever," says Angelica Pozo. In this beginner's workshop, she shows you how to enhance the surface of clay through every stage of the ceramic process, from wet clay through the glazed and fired stages and beyond." -- Provided by publisher